Improved object recognition memory using post-encoding repetitive transcranial magnetic stimulation - A.M. Heath (Elsevier, 2022)
Background: Brain stimulation is known to affect canonical pathways and proteins involved in memory. However, there are conflicting results on the ability of brain stimulation to improve to memory, which may be due to variations in timing of stimulation. Hypothesis: We hypothesized that repetitive transcranial magnetic stimulation (rTMS) given following a learning task and within the time period before retrieval could help improve memory. Methods: We implanted male B6129SF2/J mice (n = 32) with a cranial attachment to secure the rTMS coil so that the mice could be given consistent stimulation to the frontal area whilst freely moving. Mice then underwent the object recognition test sampling phase and given treatment +3, +24, +48 h following the test. Treatment consisted of 10 min 10 Hz rTMS stimulation (TMS, n = 10), sham treatment (SHAM, n = 11) or a control group which did not do the behavior test or receive rTMS (CONTROL n = 11). At +72 h mice were tested for their exploration of the novel vs familiar object. Results: At 72-h's, only the mice which received rTMS had greater exploration of the novel object than the familiar object. We further show that promoting synaptic GluR2 and maintaining synaptic connections in the perirhinal cortex and hippocampal CA1 are important for this effect. In addition, we found evidence that these changes were linked to CAMKII and CREB pathways in hippocampal neurons. Conclusion: By linking the known biological effects of rTMS to memory pathways we provide evidence that rTMS is effective in improving memory when given during the consolidation and maintenance phases.